Aeroacoustic analysis of dry ice blasting on divergent nozzle length using CFD to acoustic couple simulation - Mat, Mohamad Nur Hidayat (Springer Science and Business Media B.V., 2022)
In order to determine the effect of the divergent nozzle length on the single-hose nozzle geometry, the computational couple simulation approach was employed. Furthermore, a model was successfully provided for the two-way exchange of mass, momentum, and energy between two phases. The energy that was exchanged between two involved phases, the solid dry ice particle and a working medium of compressible air-fluid, was also obtained. The model was then coupled with the acoustic programming code solved using the Mump solver. The result revealed that the most extended divergent length showed the highest flow velocity across the nozzle cavity and induced the lowest turbulence flow. Thus, the acoustic sound pressure level was reduced. The shortest divergent nozzle length, equal to 200 mm, produced the highest sound pressure level equal to 85 dBA within the frequency range of 1000 to 1200 Hz. It also produced an average maximum of sound power level, which is 100 dB, across all frequency ranges. Therefore, this study is highly essential since the characteristics of the gas-particle flow within a nozzle cavity provide a deeper understanding of the multiphase flow in turbine and jet engine flow analysis.